Economic Empowerment Based on Islamic Philanthropy in Surabaya - Moh Arifin; Abu Sari (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2023)
Islamic philanthropy has an important role in alleviating poverty with a system of empowering the people's economy. The purpose of this study is to determine the economic empowerment of the people based on Islamic philanthropy. This study uses a type of qualitative research with an explanatory approach. Data collection uses observation, in-depth interviews, and documentation. Data analysis in this study uses interactive descriptive, where data obtained from the field is reduced, displayed and verified. The findings in this study are that the independent business group program carried out by YDSF has been able to increase people's income, so that they can reach the stage of prosperity. The business capital that is distributed comes from Islamic philanthropy which is empowered in productive activities.